Penerapan Kode Etik terhadap Profesi Akuntan di Indonesia Tantangan dan Solusi dalam Praktik Profesional - Arman Syaputra Gulo; Apriliyana Anugrah; Novi Nurfiyanti; Sheva Nabel Majid; Mey Sinta Dewi (Universitas 45 Surabaya, 2025)
The code of ethics of the public accountant profession is a moral and professional guideline that must be upheld to maintain the quality and integrity of the services provided. In the context of auditing and other accounting services, the application of ethical principles such as integrity, objectivity, professional competence, confidentiality, and professional behavior is very important to build public trust. This study aims to examine how the code of ethics is applied in public accounting practices in Indonesia, as well as the challenges faced in its implementation. The findings show that there are still external pressures, conflicts of interest, and a lack of adequate law enforcement. Therefore, it is necessary to strengthen regulations, improve ethics education, and play an active role in professional organizations to ensure that the implementation of the code of ethics is effective.